Teaching vocabulary through songs - Cepeda, María Verónica (2014)
Fil: The main objective of this work is to explore the effectiveness of teaching a foreign language through songs to improve students‟ proficiency with lexis. The study was conducted with intermediate level students at Escuela Secundaria Nº 2, in Mar del Plata. The experimental group was taught some vocabulary items with the help of selected songs and class activities including singing. The data was collected through a set of questionnaires to gather information about the students´music preferences. Afterwards, the students completed a written exam which measured the students’ lexical competence.This study suggests that teaching through songs is among one of the best methodologies to use when teaching a foreign language.